Histopathological investigation of endometrium in repeat breeder cows - DOGAN, IBRAHIM; SONMEZ, GURSEL; SAGIRKAYA, HAKAN (The Indian Journal of Animal Sciences, 2014)
This study consisted of comparative histopathological examination of endometrium in repeat breeder as well as fertile cows. In thtile and repeat breeder cows, hyperaemia, edema, and focal haemorrhages with the desquamated epithelial cells in gland lumens were observed. Subclinical endometritis was determined in 8 repeat breeder cows (53.33%). Inflammatory cell intiltration, degeneration and desquamation in the epithelial lamina, glandular dilatation and periglandular tibrosis were determined in 8 (53.33%), 5 (33.33%), 3 (20.0%) and 2 (13.33%) of cows having endometritis respectively. It was concluded that subclinical endometritis was one of the reasons of repeat breeder syndrome, and histopathological investigation on biopsies from uterine horns and body would be a useful diagnostic tool.